Building on existing tools to improve chronic disease prevention and screening in public health: a cluster randomized trial - A. K. Lofters; M. A. O'Brien; R. Sutradhar; A. D. Pinto; N. N. Baxter; P. Donnelly; R. Elliott; R. H. Glazier; J. Huizinga; R. Kyle; D. M. Manca; M. A. Pietrusiak; et al. (BMC, 2021)
Abstract Background The BETTER (Building on Existing Tools to Improve Chronic Disease Prevention and Screening in Primary Care) intervention was designed to integrate the approach to chronic disease prevention and screening in primary care and demonstrated effective in a previous randomized trial. Methods We tested the effectiveness of the BETTER HEALTH intervention, a public health adaptation of BETTER, at improving participation in chronic disease prevention and screening actions for residents of low-income neighbourhoods in a cluster randomized trial, with ten low-income neighbourhoods in Durham Region Ontario randomized to immediate intervention vs. wait-list. The unit of analysis was the individual, and eligible participants were adults age 40-64 years residing in the neighbourhoods. Public health nurses trained as "prevention practitioners" held one prevention-focused visit with each participant. They provided participants with a tailored prevention prescription and supported them to set health-related goals. The primary outcome was a composite index: the number of evidence-based actions achieved at six months as a proportion of those for which participants were eligible at baseline. Results Of 126 participants (60 in immediate arm; 66 in wait-list arm), 125 were included in analyses (1 participant withdrew consent). In both arms, participants were eligible for a mean of 8.6 actions at baseline. At follow-up, participants in the immediate intervention arm met 64.5% of actions for which they were eligible versus 42.1% in the wait-list arm (rate ratio 1.53 [95% confidence interval 1.22-1.84]). Conclusion Public health nurses using the BETTER HEALTH intervention led to a higher proportion of identified evidence-based prevention and screening actions achieved at six months for people living with socioeconomic disadvantage. Trial registration NCT03052959 , registered February 10, 2017.